أحكام عوارض دفع الشيك و تطبيقاتها على جريمة إصدار شيك بدون رصيد وفقا للتشريع الجزائري - بوخميس, منى (جامعة الوادي University of Eloued, 2017)
أنه رغم تعدد حالات عوارض الدفع إلا أن المشرع الجزائري قد ضيق من حالات و أسباب قيام عارض الدفع من خلال حصرها في حالتين و هما عدم وجود أو عدم كفاية الرصيد، و يكون بذلك قد فصل بينهما و بين حالة عدم قابلية الرصيد للتصرف فيه بسبب منع المسحوب عليه من الوفاء، رغم أنه لا يوجد فرق بينهما من حيث النتيجة و هي استحالة سداد قيمة الشيك و بالتالي تعطيله عن أداء دوره كوسيلة دفع. إن للوسطاء الماليين دور هام في الوقاية من وقوع عوارض دفع الشيك من خلال القيام بالالتزامات الواقعة على عاتقهم على أكمل وجه، بالإضافة إلى قبولهم للوفاء الجزئي على عكس ما هو جاري العمل به لدى البنوك برفض الشيكات في حالة عدم كفاية الرصيد، كما أن تحقق عارض الدفع يخضع للسلطة التقديرية للبنك الذي بإمكانه أن يجنب عميله الموثوق به الآثار المترتبة عن إصدار شيك بدون رصيد بأن يبادر بالوفاء بالشيك على المكشوف. -إن لكل من مركزية المستحقات غير المدفوعة و جهاز مكافحة إصدار الشيكات بدون رصيد باعتبارهما جهازين من بين أجهزة بنك الجزائر دور فعال في الوقاية من وقوع عوارض الدفع من خلال وضع آليات للرقابة على استعمال الشيك. - إن المشرع على إثر هذا التعديل للقانون التجاري يكون قد قضى على الازدواجية القانونية في النص على جريمة إصدار شيك بدون رصيد، محاولا بذلك توحيد الأحكام القانونية المتعلقة جرائم الشيك عموما، و ذلك بإلغائه للمادتين ( 538 ) و ( 539) من القانون التجاري و استبدل كل إحالة عليهما بالإحالة إلى المادتين ( 374 ) و ( 375) من قانون العقوبات. أنه بتكريس المشرع لفكرة تسوية عارض الدفع في القانون التجاري، فان عدم قيام الساحب بها يعد دليل إثبات على توفر سوء نيته، و بذلك يعتبر عنصر سوء النية مفترض لعلم الساحب بانعدام الرصيد أو عدم كفايته ومع ذلك لم يقم بتسويته، و بهذا فان اجتهاد المحكمة العليا في هذه النقطة أصبح يتماشى مع القانون عكس ما كان سابقا. إخضاع المتابعة الجزائية لجريمة إصدار شيك بدون رصيد إلى إجراءات أولية ذات طابع إداري تقوم بها المؤسسات المسحوب عليها، هذه الإجراءات الأولية ذات طابع إلزامي يترتب على تخلفها عدم قبول الدعوى العمومية لبطلان إجراءات المتابعة، إلا أن مجال تطبيق هذه الإجراءات لا يتعلق بصورتي قبول أو تظهير شيك صادر بدون رصيد أو برصيد غير كاف، و لا بإصدار شيك و جعله كضمان و قبوله و تظهيره، و إنما تتعلق بإصدار شيك منعدم الرصيد أو ناقص الرصيد. استقرار رأي المحكمة العليا حول طبيعة الإجراءات الأولية - و ذلك في آخر قرارتها – فبعد أن كانت تعتبرها من النظام العام تراجعت عن موقفها و أخذت بالبطلان النسبي في حالة عدم مراعاة هذه الإجراءات قبل مباشرة الدعوى العمومية. اتجاه معظم الجهات القضائية نحو الأخذ بالطابع الإلزامي للإجراءات الأولية و بالتالي توحيد الأحكام القضائية، بعد أن كان هناك تضارب فيما بينها بخصوص هذه النقطة. إمكانية تكييف أخذ المشرع بإجراءات تسوية عارض الدفع بأنها تراجع منه عن الطابع الجزائي لجريمة إصدار شيك بدون رصيد بأن أبقى على النص القانوني المجرم للفعل و هو المادة ( 374 ) من قانون العقوبات من جهة، و منح دور للبنوك في الوقاية منها بتكريس فكرة تسوية عارض الدفع. Despite the multiplicity of cases of payment symptoms, the Algerian legislator has narrowed the cases and reasons for the payment of the plaintiff by limiting them in two cases, namely, the lack or inadequacy of the balance, thus separating them from the case of the inability of the balance to act because of the prohibition Withdrawing from the fulfillment, although there is no difference between them in terms of the result is the impossibility of payment of the value of the check and thus disable it from performing its role as a means of payment. - The financial intermediaries have an important role in preventing the occurrence of the symptoms of payment of the check by carrying out their obligations to the fullest, in addition to their acceptance of the partial payment contrary to what is going on with the banks to refuse checks in case of insufficient balance, Payment is subject to the discretion of the bank, which can avoid its reliable customer the effects of issuing a check without credit to initiate the check on overdraft. - Each of the centralization of unpaid receivables and the anti-issuance of checks without balance as two of the organs of the Bank of Algeria has an effective role in the prevention of the occurrence of payment symptoms through the establishment of mechanisms to control the use of the check. - The legislator, following this amendment to the Commercial Law, has eliminated the legal duplication in the provision of a check without a balance, trying to unify the legal provisions relating to check crimes in general, by repealing Articles 538 and 539 of the Commercial Law and replacing Each referring to them by reference to articles 374 and 375 of the Penal Code. - The fact that the legislator consents to the idea of settlement of payment in commercial law, the non-presence of the drawer is proof of the existence of his ill-intention, and therefore the element of bad faith presumed to be aware of the lack of the balance or lack of adequacy and yet did not resolve it, Supreme in this point became in line with the law reversed what it was previously. - Subjecting penal follow-up to the offense of issuing a check without balance to preliminary procedures of an administrative nature by the withdrawing institutions. These initial procedures are of a mandatory nature, and the failure of the public prosecution to invalidate the public proceedings is void. However, the scope of these procedures is not related to the forms of acceptance or endorsement Check issued with no balance or insufficient balance, and not issuing a check and make it as security and acceptance and endorsement, but the issuance of a check without a balance or minus the balance. - Stability of the opinion of the Supreme Court on the nature of the preliminary procedures - and in the last decision - after it was considered from the public order declined its position and took the relative void in the event that these procedures are not observed before the commencement of the public prosecution. - The tendency of most judicial bodies to adopt the mandatory nature of the preliminary proceedings and thus the unification of the judicial decisions, after there was a conflict between them on this point. - The possibility of adapting the legislator to take the procedures of payment settlement as a retreat from the criminal nature of the crime of issuing a check without balance by keeping the criminal text of the act, article 374 of the Penal Code, on the one hand, paying off.
قانون أعمال
Keywords: الشيك – الدفع – الرصيد; Check - Payment - Balance